L’anthropologue effondré. Récit d’un enquêteur malade - Etienne Quinn (Anthropologie & Santé)
This article recounts the author’s misadventure that occurred during ethnographic fieldwork. While he was conducting a survey of agricultural practices in a small village in the Sierra Nevada (Andalusia, Spain), the anthropologist contracted a high fever that left him bedridden for about ten days, arousing the sympathy of the village’s inhabitants. Based on this experience as a sick person in the field, the author discusses the relationship between the investigator/interviewee, revealing the tension between distance and immersion, methodological rigor and ethnographic flexibility, and raising the question of the anthropologist’s positioning with regard to those with whom he shares everyday life, within the context of care.